Building a digital repository program with limited resources - Clobridge, Abby (Chandos information professional series., 2010)
Whether you are just starting to create a digital repository or your institution already has a fully developed program, Building a Digital Repository Program with Limited Resources provides strategies for building and maintaining a high-use, cohesive, and fiscally responsible repository with collections that showcase your institution. Author Abby Clobridge explains how to strategically select projects tied to your institution's goals, create processes and workflows designed to support a fully functioning program, and creatively utilize existing resources. She discusses the benefits of taking a holistic approach to creating a digital repository program rather than focusing only on individual collections. The book includes ready-to-use templates, worksheets, workshop exercises, and assessment tools, along with practical and easily adoptable case studies. It will be useful guidebook to building and sustaining digital repository programs.